Answer:
x= 4 or <
Step-by-step explanation:
We have two solutions for this problem based on the given equation.
<u><em>Answer #1:</em></u>
<u>If the given equation was:</u>
![f + \frac{4}{g} = 6](https://tex.z-dn.net/?f=%20f%20%2B%20%5Cfrac%7B4%7D%7Bg%7D%20%3D%206%20)
To solve for f, we would need to isolate the "f" on one side of the equation.
In case of the above equation, we can simply do that by subtracting
from both sides of the equation
<u>This would give:</u>
f +
-
= 6 - ![\frac{4}{g}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7Bg%7D%20%20)
f = 6 - ![\frac{4}{g}](https://tex.z-dn.net/?f=%20%5Cfrac%7B4%7D%7Bg%7D%20%20)
<u><em>Answer #2:</em></u>
<u>If the given equation was:</u>
![\frac{f+4}{g} = 6](https://tex.z-dn.net/?f=%20%5Cfrac%7Bf%2B4%7D%7Bg%7D%20%3D%206%20)
To solve for f, we would still need to isolate the "f" on one side of the equation.
<u>This can be done as follows:</u>
................> multiply both sides by (g)
f + 4 = 6g ................> subtract 4 from both sides of the equation
f + 4 - 4 = 6g - 4
f = 6g - 4
Hope this helps :)
Answer:
1 and 1/6 cups of flour
Step-by-step explanation:
We need the fractions to have common denominators so multiply 1/2 by 3 and 2/3 by 2 to get the common denominator of 6.
1/2 x 3/3 = 3/6
2/3 x 2/2 = 4/6
Add the two fractions
3/6 + 4/6 = 7/6 or 1 & 1/6